Incidencia del impuesto a los consumos especiales en la rentabilidad de la compañia limitada de televisión pagada ATV Cable en la ciudad de Latacunga durante los periodos 2007-2008. - Changoluisa Quishpe, Jessica Maribel (2017)
The research project aimed to determine the Incidence of Taxes on Special Consumption in the profitability of the ATV Cable Company for the paid television services during the period 2007 to 2008. For the execution of the study it was indispensable to gather information using the exploratory research that allowed to increase the familiarity with the phenomenon to be studied, and descriptive that helped to know the characteristics of the situation prevailing at the time to carry out the study, descriptive methodology was used because it allows to know and to identify if the variation that occurred within the tax affected or not to the company, documents through which the data that have been obtained will be investigated and interpreted analytically to describe better the problem in small components to determine the main variants and statistics that allowed the tabulation of the results of the research, with techniques and research instruments such as the interview addressed to the owner -manager of the company and the public workers of Servicio de Rentas Internas, the survey was directed to the company's officials and the final consumer of the service. Finally, the direct observation to the financial statements allowed the collection of information for the fulfillment of the proposed objective and the interpretation and analysis that verified the hypothesis that was obtained. The main conclusions of this research are the following; the company and the consumers of the service were affected by the implementation of this tax, since when increasing the value to pay, several users suspended the service affecting the economy of the company, the investigation showed that if there was a notable incidence in the profitability of the company, visualizing during this period a decrease of the revenues for the paid television services, this affirmation is checked with the answer of the interview to the manager who mentions that during the year that the tax was implemented the users suspended the service thus diminishing the company´s utility.